Pengembangan Sistem Manajemen Layanan Pernikahan Berbasis Web (Studi Kasus: KUA Dawarblandong - Mojokerto) - Nadya Dwi Sukmawati; Denny Sagita Rusdianto; Eriq Muhammad Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The Office of Religious Affairs has a role in religious matters, especially marriage. In improving the function, KUA Dawarblandong use the